1990
DOI: 10.2307/2048270
|View full text |Cite
|
Sign up to set email alerts
|

Generic Homeomorphisms have the Pseudo-Orbit Tracing Property

Abstract: Abstract.Let M (dimA/<3) be a compact manifold. Then a generic fe Homeo(A/) satisfies the following: / has the pseudo-orbit tracing property; / is C tolerance stable; and / is not topologically stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The study of the invariant measures for typical maps was initiated recently by Abdenur and Andersson [AA]. Previously studies of the dynamics of typical maps have concentrated on the topological properties; see [AHK,AP,H1,H2,KMOP,O,OU,PP,Y] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the invariant measures for typical maps was initiated recently by Abdenur and Andersson [AA]. Previously studies of the dynamics of typical maps have concentrated on the topological properties; see [AHK,AP,H1,H2,KMOP,O,OU,PP,Y] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, many genericity results exist for manifolds. Yano [37] demonstrated that shadowing is generic among homeomorphisms of the unit circle, Odani [26] extended this result to smooth manifolds of dimension at most three, and Pilyugin and Plamenevskaya [31] further extended this result to compact manifolds without boundary which have a handle decomposition. Results concerning the more general class of continuous maps include those of Mizera [24], who demonstrated that shadowing is generic in C(X) where X is an arc or circle, and those of Kościelniak, Mazur, Oprocha and Pilarczyk [18], who extended this result to C(X) and S(X) where X is a compact manifold.…”
mentioning
confidence: 99%